2013
DOI: 10.1007/s00270-013-0606-2
|View full text |Cite|
|
Sign up to set email alerts
|

British Society of Interventional Radiology (BSIR) Inferior Vena Cava (IVC) Filter Registry

Abstract: Purpose The British Society of Interventional Radiology (BSIR) Inferior Vena Cava (IVC) Filter Registry was produced to provide an audit of current United Kingdom (UK) practice regarding placement and retrieval of IVC filters to address concerns regarding their safety. Methods The IVC filter registry is a web-based registry, launched by the BSIR on behalf of its membership in October 2007. This report is based on prospectively collected data from October 2007 to March 2011. This report contains analysis of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 17 publications
1
72
1
2
Order By: Relevance
“…Procedural codes were utilized to identify VCF placement; however, these codes are not specific to permanent or retrievable devices. As of 2006, retrievable devices made up about 85% of the VCF market in the United States, which likely increased to >90% since then 38, 39, 40, 41. Therefore, the retrieval estimates presented here are underestimated.…”
Section: Discussionmentioning
confidence: 84%
“…Procedural codes were utilized to identify VCF placement; however, these codes are not specific to permanent or retrievable devices. As of 2006, retrievable devices made up about 85% of the VCF market in the United States, which likely increased to >90% since then 38, 39, 40, 41. Therefore, the retrieval estimates presented here are underestimated.…”
Section: Discussionmentioning
confidence: 84%
“…As of 2006, retrievable devices made up about 85% of the VCF market in the United States, which likely increased to >90% since then. [38][39][40][41] Therefore, the retrieval estimates presented here are underestimated. Assuming that 10% to 20% of all VCFs used are permanent and thus cannot be retrieved, this would make our estimated retrieval 26% to 30%, making this corrected estimate near previous estimates of national retrieval rates of 30%.…”
Section: Limitationsmentioning
confidence: 91%
“…4,5 The British Society of Interventional Radiology (BSIR) recently evaluated placement and retrieval of 1434 IVC filters and reported that ....................................................................................................................... 88 patients demonstrated new lower limb DVT and/or IVC thrombosis following IVC filter placement. 6 At the present time, there is no reported consensus to establish routine surveillance guidelines of IVC filters; however, there are guidelines encouraging IVC device retrievals when the duration of treatment for a DVT/PE has been met or when the risk of a PE is no longer high, and/or the contraindication for anticoagulation is no longer a consideration. 7 In this case, the noninvasive renal artery duplex examination played a critical role in her clinical outcome.…”
Section: Discussionmentioning
confidence: 99%